Excision repair of ultraviolet damage in mammalian cells. Evidence for two steps in the excision of pyrimidine dimers. - Williams, J I (1978)
The incidence of pyrimidine dimer formation and the kinetics of DNA repair in African green monkey kidney CV-1 cells after ultraviolet (UV) irradiation were studied by measuring survival, T4 endonuclease V-sensitive sites, the fraction of pyrimidine dimers in acid-insoluble DNA as determined by thin layer chromatography (TLC), and repair replication. CV-1 cells exhibit a survival curve with extrapolation number n = 7.8 and Do = 2.5 J/m2. Pyrimidine dimers were lost from acid-insoluble DNA more slowly than endonuclease-sensitive sites were lost from or new bases were incorporated into high molecular weight DNA during the course of repair. Growth of CV-1 cultures in [3H]thymidine or X-irradiation (2 or 10 krads) 24 h before UV irradiation had no effect on repair replication induced by 25 J/m2 of UV. These results suggest that pyrimidine dimer excision measurements by TLC are probably unaffected by radiation from high levels of incorporated radionuclides. The endonuclease-sensitive site and TLC measurements can be reconciled by the assumption that pyrimidine dimers are excised from high molecular weight DNA in acid-insoluble oligonucleotides that are slowly degraded to acid-soluble fragments.